Eu quero, eu posso?: implementação e efetividade de políticas públicas: um estudo do Programa Trabalho e Empreendedorismo da Mulher em Pernambuco - Silva, Géssika Cecília Carvalho da (2015)
This thesis aims to understand the process of implementation of the Programa Trabalho e Empreendedorismo da Mulher in Pernambuco (PTEM) and its benefits for women who participated in its activities. For this research of qualitative nature were used as methodological tools a documentary and literature search, interviews with managers and with beneficiaries of the policy note and still a content analysis explained in textbooks used in courses and workshops. As models of analysis, considering the institutional and process models, by Thomas Dye (2009) and by the academic function of Silva and Silva (2008). The survey results showed that the PTEM-PE had its merits and has brought benefits to the participants, although not necessarily the objective for the Program, as have more subjective, behavioural and existential aspects. Confirmed also the issues related to our guiding hypotheses, the format applied to implementation of this Program in Pernambuco not contemplated the local’s reality and had results other than those achieved by the initial experience in Rio de Janeiro. This due to the fact that in this state of the policy was the result of a project that had significant results, prior experience and that opened up a way for correction of distortions and adjustments needed, what didn't happen in Pernambuco; and in Rio de Janeiro also had as a differential aspect of women having an after ativities monitoring from this Program, a support in the management of businesses and groups. We had highlighted among the challenges still in the process of implementation the limitations of partnerships, not to forecast financial resources to ensure the transportation of the participants and the leasing spaces to carry out the activities.